MICROHABITATS OF Hylarana chalconota ALONG FAST FLOWING WATER STREAMS IN DEGRADED LAND IN GUNUNG SALAK FOOT HILL - Hellen Kurniati; Alex Sumadijaya (Pusbindiklat - LIPI, 2011)
This research was conducted to determine the microhabitat selection in the frog species Hylarana chalco-nota in fl owing aquatic habitats situated in degraded land. Three survey sites (river, ditch, pine plantation) were selected in the Curug Nangka area on the slopes of Gunung Salak at an altitude between 630–740 m above sea level. Transect methodology was used to determine the microhabitat preference in H. chalconota. Two ways paired and one-way ANOVA were used to test the impact of environmental factors on the microhabitat preference of H. chalconota. A signifi cant effect of air humidity on the presence of individual frog in the river and pine plantations was observed, but other environmental factors (air temperature, water temperature, air humidity, moon phase) had no signifi cant effect on individual H. chalconota along the ditch irrigation. In selecting microhabitats, the frog prefers vegetation below the substrate. However, frogs did not select specifi c plant species;preference appears to be related to the nature of the leaf and petiole strength. In horizontal microhabitat selection, individual frog tend to choose a distance between 0-1 meters from the edge of a river or ditch, while in vertical microhabitat selection, individual H. chalconota tend to choose a distance between 0–1 m from the ground.